2006
DOI: 10.1149/1.2215560
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Y2Ru2O7 and Y2-XPrXRu2O7 for Cathode Application in Intermediate Temperature Solid Oxide Fuel Cells

Abstract: Nanocrystalline powders of Y2Ru2O7 and Y2-xPrxRu2O7 were prepared by a co-precipitation method. Pr was chosen as the A- site dopant in order to increase the electrical conductivity of Y2Ru2O7. Phase and morphology were studied by XRD and FE- SEM, which showed both systems exhibit a particle size of about 100 nm, and the doped powders were single pyrochlore phase. The electrical conductivity of a dense bar of Y2- xPrxRu2O7 was measured at several temperatures by d.c. 4-probe method, while the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…18 The low resistance ͑3.47 and 0.08 ⍀ cm 2 at 500 and 700°C, respectively͒ of this composite may be attributable in part to the high ionic conductivity of the ESB20 phase. In addition, ruthenium oxides are known to be catalytically active, 19,20 and by selection of a sufficiently large A-site dopant cation in ͑A 2 Ru 2 O 7 ͒, such as Pb or Bi, its band structure is altered in such a way as to render its behavior metallic, with conductivity increasing as temperature decreases. 21 For this study, bismuth was chosen as the A-site dopant, as it is the same as the host cation of the ESB20 phase and should improve chemical compatibility.…”
Section: ••mentioning
confidence: 99%
“…18 The low resistance ͑3.47 and 0.08 ⍀ cm 2 at 500 and 700°C, respectively͒ of this composite may be attributable in part to the high ionic conductivity of the ESB20 phase. In addition, ruthenium oxides are known to be catalytically active, 19,20 and by selection of a sufficiently large A-site dopant cation in ͑A 2 Ru 2 O 7 ͒, such as Pb or Bi, its band structure is altered in such a way as to render its behavior metallic, with conductivity increasing as temperature decreases. 21 For this study, bismuth was chosen as the A-site dopant, as it is the same as the host cation of the ESB20 phase and should improve chemical compatibility.…”
Section: ••mentioning
confidence: 99%
“…Accordingly, trivalent yttrium ions can be considered as A-site cations of the pyrochlore oxide because of the similar ionic radius with that of divalent lead or trivalent bismuth ions . On the basis of the Mott–Hubbard mechanism, the electrical behavior of the pyrochlore oxide is determined by the Ru–O–Ru bond angle, which corresponds with the size of A-site cations. , In this regard, the development of yttrium ruthenate (Y 2 [Ru 2– x Y x ]­O 7– y ) as a new electrocatalyst is needed for an extensive understanding of pyrochlore structure.…”
mentioning
confidence: 99%
“…25 On the basis of the Mott−Hubbard mechanism, the electrical behavior of the pyrochlore oxide is determined by the Ru−O−Ru bond angle, which corresponds with the size of A-site cations. 26,27 In this regard, the development of yttrium ruthenate (Y 2 [Ru 2−x Y x ]O 7−y ) as a new electrocatalyst is needed for an extensive understanding of pyrochlore structure.…”
mentioning
confidence: 99%
“…However, several ruthenate compounds and noble metals showed their reliability and long-term stability as cathodes on ESB. 13,30,31 In the case of BIMEVOX, the electrode composition still represents an unsolved problem because of their tendency to react 32 and alloy with most cathode materials, including noble metals. Boukamp observed that Au and Pt electrodes on BICUVOX modify their morphology, while sputtered Ag electrodes disappear completely after the electrochemical test in oxygen redox conditions.…”
mentioning
confidence: 99%